Impact of Brand Personality on Brand Equity: The Role of Brand Trust, Brand Attachment, and Brand Commitment - Ahmad, Anees; Thyagaraj, K. S. (Indian Journal of Marketing, 2015)
Research suggests a close interrelationship between brand personality and brand equity. Companies have recognized the importance of brand personality in the development of brand equity. Therefore, a brand management strategy based on interrelationship between brand personality and brand equity is the need of the hour. The purpose of this study was to understand the influence of brand personality on brand equity through relational variables: brand trust, brand attachment, and brand commitment and to offer a model depicting the relationship among these variables. The data were collected from a survey of 220 respondents. Structural equation modeling was used to test the proposed model. The results of the study confirm the indirect influence of brand personality on brand equity via brand trust, brand attachment, and brand commitment. The findings yield implications for brand managers, which will help them in devising branding strategies.